High performance poly(isatin alkyl-terphenyl)s proton exchange membranes with flexible alkylsulfonated side groups. (September 2022) - Wang, Yannan; Wang, Yajie; Guo, Maolian; Ban, Tao; Zhu, Xiuling
Hydrocarbon-based polymer proton exchange membranes (PEMs) free of heteroatom linkages are supposed to be an attractive alternative for the most advanced perfluorosulfonic acid PEMs, but it is challenging to synthesize them. Here we disclosed a series of aliphatic chain-containing poly(isatin diphenyl-co-terphenyl)(PIDT) copolymers, which were conveniently prepared by superacid-catalyzed Friedel-Crafts polycondensation. Subsequently, the sulfonated copolymer (SPIDT) membranes were prepared by the grafting of side-chain sulfonic acid groups. Due to the formed continuous and efficient nanoscale proton transport channel, these PEMs exhibited excellent proton conductivity showing 186 mS/cm at 80°C, higher than Nafion115 (150 mS/cm). Meanwhile, the prepared membranes exhibited good oxidative stability. The residual weight of the membranes is still greater than 98 wt % after 1 h immersion in Fenton's reagent at 80°C. Notably, the direct borohydride-hydrogen fuel cell (DBHFC) equipped with SPIDT-50 membrane as the diaphragm showed the peak power density of 71 mWcm −2 at 25°C, which was greater than that of Nafion115 (63 mWcm −2 ). Therefore, the hydrocarbon-based PEMs prepared in this study show promise for application in fuel cells.